Preparation of high‐purity ammonium tetrakis(Pentafluorophenyl)borate for the activation of olefin polymerization catalysts - Lee, Hyun Ju; Baek, Jun Won; Seo, Yeong Hyun; Lee, Hong Cheol; Jeong, Sun Mi; Lee, Junseong; Lee, Chong Gu; Lee, Bun Yeoul (Molecules, 2021)
Homogeneous olefin polymerization catalysts are activated in situ with a co‐catalyst ([PhN(Me)2‐H]+[B(C6F5)4]− or [Ph3C]+[B(C6F5)4]−) in bulk polymerization media. These co‐catalysts are insoluble in hydrocarbon solvents, requiring excess co‐catalyst (>3 eq). Feeding the activated species as a solution in an aliphatic hydrocarbon solvent may be advantageous over the in situ activation method. In this study, highly pure and soluble ammonium tetrakis(pentafluorophenyl)borates ([Me(C18H37)2N‐H]+[B(C6F5)4]− and [(C18H37)2NH2]+[B(C6F5)4]−) containing neither water nor Cl− salt impurities were prepared easily via the acid–base reaction of [PhN(Me)2‐H]+[B(C6F5)4]− and the corresponding amine. Using the prepared ammonium salts, the activation reactions of commercial-process‐relevant metallocene (rac‐[ethylenebis(tetrahydroindenyl)]Zr(Me)2 (1‐ZrMe2), [Ph2C(Cp)(3,6‐tBu2Flu)]Hf(Me)2 (3‐HfMe2), [Ph2C(Cp)(2,7‐thBu2Flu)]Hf(Me)2 (4‐HfMe2)) and half‐me-tallocene complexes ([(5‐Nk‐Me4C5)Si(Me)2(thBu)]Ti(Me)2 (5‐TiMe2), [(5h‐N))]Ti(Me)2 (6‐TiMe2), and [(k‐Me4C5)(C9H9(5‐N))]Ti(Me)2 (7‐TiMe2)) were monitored in C6D12 withk‐Me3C7H1S)(C10H11(1H NMR spectroscopy. Stable [L‐M(Me)(NMe(C18H37)2)]+[B(C6F5)4]− species were cleanly generated from 1‐ZrMe2, 3‐HfMe2, and 4‐HfMe2, while the species types generated from 5‐TiMe2, 6‐TiMe2, and 7‐TiMe2 were unstable for subsequent transformation to other species (presumably, [L‐ Ti(CH2N(C18H37)2)]+[B(C6F5)4]−‐type species). [L‐TiCl(N(H)(C18H37)2)]+[B(C6F5)4]−‐type species were also prepared from 5‐TiCl(Me) and 6‐TiCl(Me), which were newly prepared in this study. The prepared [L‐M(Me)(NMe(C18H37)2)]+[B(C6F5)4]−‐, [L‐Ti(CH2N(C18H37)2)]+[B(C6F5)4]−‐, and [L‐ TiCl(N(H)(C18H37)2)]+[B(C6F5)4]−‐type species, which are soluble and stable in aliphatic hydrocarbon solvents, were highly active in ethylene/1‐octene copolymerization performed in aliphatic hydrocarbon solvents.
Keywords: Activation reaction; Ammonium tetrakis(pentafluoro-phenyl)borate; Half‐metallocene; Metallocene; Olefin polymerization